Developing and using monitoring programs for fresh cows - Smith, John F., 1962-; Harner, Joseph P.; Brouk, Michael J. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Metabolic disorders and related health problems are a significant problem on dairy farms, resulting in increased culling and decreased profitability for producers. Early detection and treatment of disorders and disease is critical in minimizing losses and increasing probability of cow recovery. Fresh cow monitoring systems that evaluate several key factors – general appearance, body temperature, intake or appetite, rumen motility, milk production, and milk or urine concentrations of ketones – are necessary for early detection of disorders and disease. Most of these problems occur within the first 3 weeks of lactation, with most occurring during the first 10 days. Developing and implementing of fresh cow monitoring systems and early treatment should increase profitability of dairy enterprises by reducing the negative effects of metabolic disorders and forced early culling.
Keywords: Dairy; Health; Calving; Metabolic disorders